2013
DOI: 10.1155/2013/189843
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Foetal Cardiovascular Effects of the Anaesthetic Alfaxalone in 2‐Hydroxypropyl‐β‐cyclodextrin in the Pregnant Ewe

Abstract: The objective of this study was to determine the pharmacodynamics effects of the anaesthetic alfaxalone in 2-hydroxypropyl-β-cyclodextrin in pregnant sheep after the intravenous injection of a 2 mg/kg weight dose. Six pregnant Ripollesa sheep, weighing 47.1 ± 4.4 kg, were used. Twenty-four hours after instrumentation, sheep were anaesthetized with intravenous alfaxalone in cyclodextrin. Time to standing from anaesthesia was 30.0 ± 10.81 min. Foetal heart rate increased significantly during the first 5 min afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…15 These results are consistent with other studies but the fetus can survive because of specific adaptations enabling high oxygen delivery to fetal tissues and organs. 15,16 Factors contributing to the development of ventilation and perfusion mismatching include the pregnancy status of the sheep, the supine position and the Trendelenburg position. 6 Although the pulmonary complications of anaesthesia and recumbency in sheep contribute to the risk of anaesthetic-related complications they can be managed and did not appear to cause any detrimental effects in either the ewe or the fetuses in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 These results are consistent with other studies but the fetus can survive because of specific adaptations enabling high oxygen delivery to fetal tissues and organs. 15,16 Factors contributing to the development of ventilation and perfusion mismatching include the pregnancy status of the sheep, the supine position and the Trendelenburg position. 6 Although the pulmonary complications of anaesthesia and recumbency in sheep contribute to the risk of anaesthetic-related complications they can be managed and did not appear to cause any detrimental effects in either the ewe or the fetuses in this study.…”
Section: Discussionmentioning
confidence: 99%
“…15 These results are consistent with other studies but the fetus can survive because of specific adaptations enabling high oxygen delivery to fetal tissues and organs. 15,16…”
Section: Discussionmentioning
confidence: 99%
“…Alpacas, goats and sheep are among the ruminants in which the anesthetic effect of alfaxalone-HPCD alone has been investigated [ 2 , 3 , 6 , 8 ]. del Álamo et al [ 6 ] reported that the dose sufficient to allow endotracheal intubation was 2.1 ± 0.1 mg/kg, and the time from induction to standing was 34.1 ± 3.2 min in 5 alpacas (weight: 96.7 ± 19.9 kg) anesthetized with alfaxalone-HPCD alone.…”
Section: Discussionmentioning
confidence: 99%
“…A single bolus of alfaxalone produced longer recoveries in pregnant than in non‐pregnant ewes (Andaluz et al. ). As a consequence, it has been recommended to reduce drug dosage by 25% in pregnant animals.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy may produce alterations in uptake, distribution and disposition of anaesthetic agents (Raffe & Carpenter 2007). A single bolus of alfaxalone produced longer recoveries in pregnant than in non-pregnant ewes (Andaluz et al 2013). As a consequence, it has been recommended to reduce drug dosage by 25% in pregnant animals.…”
Section: Discussionmentioning
confidence: 99%